Poverty Alleviation Through Sustainable Tourism: Amanhecer Plan analysis - D’Angelis, Bruna Carolina Stankys; Silva, Rodrigo Freire de Carvalho e (Revista Turismo em Análise, 2014)
New paradigms of poverty alleviation have been formulated by the United Nations (UN) and, believing in the tourism potential in generating inclusion through the work, the increased income and the social welfare of the population, were also adopted by World Tourism Organization (UNWTO) and the Brazilian Ministry of Tourism. Thus, this paper seeks to study poverty alleviation through tourism, verifying the propositions for the development of tourism in Paraíba presented by Amanhecer Plan, from the State Government (2000). This is a qualitative research, through a literature and documentary review, that seeks to understand the relationships between tourism, sustainability and poverty alleviation. The Amanhecer Plan had as objective the development of sustainable tourism considering for such a tourist satisfaction, minimal environmental and cultural impacts, citizen satisfaction and return on investment. A basic condition for the growth of tourism in Paraiba was the development of integrated social, economic and urban and natural resource preservation. This is a plan with short comings despite the already dealing with sustainable tourism, does not work with concrete actions and projects prepared for such an event. Moreover, it is one more in the luggage of Paraíba state, which suffers from discontinuities, mainly for political reasons.